Plateau Rayleigh Instability Simulation - Mead-Hunter, Ryan; King, Andrew; Mullins, Benjamin (American Chemical Society, 2012)
The well-known phenomena of Plateau–Rayleigh instability has been simulated using computational fluid dynamics (CFD). The breakup of a liquid film into an array of droplets on a cylindrical element was simulated using a volume-of-fluid (VOF) solver and compared to experimental observations and existing theory. It is demonstrated that the VOF method can correctly predict the breakup of thins films into an array of either axisymmetric droplets or clam-shell droplets, depending on the surface energy. The existence of unrealistically large films is precluded. Droplet spacing was found to show reasonable agreement with theory. Droplet motion and displacement under fluid flow was also examined and compared to that in previous studies. It was found that the presence of air flow around the droplet does not influence the stable film thickness; however, it reduces the time required for droplet formation. Novel relationships for droplet displacement were derived from the results.